SISTEM PERADILAN ISLAM - Gunawan, Hendra (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2019)
Today, Islam is not sufficiently known as iqtisad (the Islamic banking system) which is now quite the belle of this beloved pancasila earth, but along with that Islam is also known as the administration of justice and its ability to protect people's rights which is then called the sharia court. The person most responsible for implementing this Islamic court is the caliph and qadhi (judge). The Caliph carries out Islamic laws and applies them to all the people while the judge takes Islamic decisions based on the Qur'an and the Sunnah. Because in the teachings of Islam do not submit the determination of justice to the will on the basis of human taste but the authority to make the law is only Allah SWT, the Creator of man and the All-Knowing about the human self